Influence of the pulp of Mangifera indica and Myrciaria dubia on the bioactive and sensory properties of ice cream - Mauricio-Sandoval, Enrique Alonso; Espinoza-Espinoza, Luis Alfredo; Ruiz-Flores, Luis Alberto; Valdiviezo-Marcelo, Jaime; Moreno-Quispe, Luz Arelis; Cornelio-Santiago, Heber Peleg (Frontiers in Sustainable Food Systems, 2023)
Ice cream is a widely consumed product in the world. Unfortunately, its standard presentation is very poor in nutraceuticals; fruits such as Mangifera indica and Myrciaria dubia have an important bioactive potential, which can be used to enrich this type of product in phytochemicals. However, maintaining the health and sensory aspects of a functional ice cream is still under investigation. The influence of Mangifera indica and Myrciaria dubia pulp on the bioactive and sensory properties of ice cream was studied. Four ice cream treatments were prepared with Mangifera indica (15% and 20%) and Myrciaria dubia (5% and 10%). Ascorbic acid content (reduction of 2,6 dichlorophenolindophenol), total phenolic content (Folin-Ciocalteu reaction) and antioxidant capacity (DPPH radical inhibition) were evaluated in addition to a sensory sorting test. The treatments with 10% Myrciaria dubia showed the highest ascorbic acid contents (83.46 and 71.27 mg/100g), total phenolic compounds (80.10 and 79.06 mgGAE/100g) and antioxidant capacity (61.0 and 64.05 mg ice/ml solvent) compared to the 5% treatment and the control; while the influence of Mangifera indica on these parameters was relatively minor. However, sensory evaluation showed that T3 (5% Myrciaria dubia; 20% Mangifera indica) were the most preferred, outperforming the control ice cream. It is evident that Myrciaria dubia stands out for its high ascorbic acid content, total phenolic compounds and antioxidant capacity of the ice cream while Mangifera indica improves its sensory aspect, allowing an overall balance of sweet-acid taste pleasant to the consumer and maintaining its health properties.